Adherence to treatment of chronic hepatitis C: from interferon containing regimens to interferon and ribavirin free regimens. Issue 28 (July 2016) - Younossi, Zobair M.; Stepanova, Maria; Henry, Linda; Nader, Fatema; Younossi, Youssef; Hunt, Sharon
Abstract : Abstract: Patients' experience during treatment may affect treatment adherence. Our aim was to assess the impact of patient-reported outcomes (PROs) on adherence to different anti-hepatitis C virus (HCV) regimens. Clinical, demographic, and PRO data (short form-36 [SF-36], chronic liver disease questionnaire-hepatitis C version [CLDQ-HCV], functional assessment of chronic illness therapy-fatigue [FACIT-F], work productivity and activity impairment: specific health problem [WPAI:SHP]) from 13 multinational clinical trials of anti-HCV treatment were available. Treatment adherence was defined as >80% of prescribed doses taken. Included were 4825 HCV patients. Regimens were grouped into: interferon- and ribavirin (RBV)-containing (±sofosbuvir [SOF]), interferon-free RBV-containing (RBV + SOF ± ledipasvir [LDV]), and interferon-free RBV-free (LDV/SOF). The adherence to these regimens were 77.6%, 84.3%, and 96.2%, respectively ( P < 0.0001). Nonadherent patients were more likely to be unemployed and to have a greater PRO impairment at baseline (up to −5.3% lower PRO scores, P < 0.0001). During treatment with interferon- or RBV-based regimens, nonadherent patients experienced lower PROs and had larger decrements from their baseline PRO scores. In contrast, there were no significant declines in PRO scores (all P > 0.05) for the small number of patients who were nonadherent to LDV/SOF. In multivariate analysis, being treatment-naive, longer treatment duration, and receiving an interferon- or RBV-containing regimen were associated with a lower likelihood of adherence (all P < 0.003). Better baseline and on-treatment PRO scores were associated with a higher likelihood of adherence to interferon and RBV. The use of interferon and/or RBV, longer duration of treatment, and lower baseline and on-treatment PRO scores were linked to a decreased likelihood of being adherent to interferon + RBV-containing or interferon-free RBV-containing antiviral regimens. Interferon- and RBV-free regimens were associated with excellent adherence. Abstract : Supplemental Digital Content is available in the text